The impact of PROGRESA on women's status and intrahousehold relations - Adato, Michelle; de la Briere, Benedicte; Mindek, Dubravka; Quisumbing, Agnes R. (International Food Policy Research Institute, 2003)
Since 1997 Mexico has provided poor families with cash benefits linked to children’s school attendance and regular clinic attendance, as well as in-kind health benefits and nutritional supplements, through the Programa Nacional de Educación, Salud y Alimentación (PROGRESA). Unlike previous social programs in Mexico, this nationwide antipoverty program targets transfers to the mother of the family. Planners deliberately decided to give transfers directly to the mother because of the growing literature that finds that resources controlled by women are more likely to be manifested in greater improvements in child health and nutrition than resources controlled by men.